Uniqueness of solutions to integrodifferential and functional integrodifferential equations. (1999) - Bahuguna, D.; Garey, L. E.
Abstract : In this paper we study a class of integrodifferential and functional integro-differential equations with infinite delay. These problems are reformulated as abstract integrodifferential and functional integrodifferential equations. We use Nagumo type conditions to establish the uniqueness of solutions to these abstract equations.